High Antibodies to VAR2CSA in Response to Malaria Infection Are Associated With Improved Birthweight in a Longitudinal Study of Pregnant Women - McLean, Alistair R. D.; Opi, D. Herbert; Stanisic, Danielle I.; Cutts, Julia C.; Feng, Gaoqian; Ura, Alice; Mueller, Ivo; Rogerson, Stephen J.; Beeson, James G.; Fowkes, Freya J. I. (Frontiers in Immunology, 2021)
Introduction: Pregnant women have an increased risk of P. falciparum infection, which is associated with low birth weight and preterm delivery. VAR2CSA, a variant surface antigen expressed on the parasitized erythrocyte surface, enables sequestration in the placenta. Few studies have prospectively examined relationships between antibody responses during pregnancy and subsequent adverse birth outcomes, and there are limited data outside Africa. Methods: Levels of IgG against VAR2CSA domains (DBL3; DBL5) and a VAR2CSA-expressing placental-binding P. falciparum isolate (PfCS2-IE) were measured in 301 women enrolled at their first visit to antenatal care which occurred mid-pregnancy (median = 26 weeks, lower and upper quartiles = 22, 28). Associations between antibody levels at enrolment and placental infection, birthweight and estimated gestational age at delivery were assessed by linear and logistic regression with adjustment for confounders. For all outcomes, effect modification by gravidity and peripheral blood P. falciparum infection at enrolment was assessed. Results: Among women who had acquired P. falciparum infection at enrolment, those with higher levels of VAR2CSA antibodies (75th percentile) had infants with higher mean birthweight (estimates varied from +35g to +149g depending on antibody response) and reduced adjusted odds of placental infection (aOR estimates varied from 0.17 to 0.80), relative to women with lower levels (25th percentile) of VAR2CSA antibodies. However, among women who had not acquired an infection at enrolment, higher VAR2CSA antibodies were associated with increased odds of placental infection (aOR estimates varied from 1.10 to 2.24). Conclusions: When infected by mid-pregnancy, a better immune response to VAR2CSA-expressing parasites may contribute to protecting against adverse pregnancy outcomes.